Impact of Agro-environmental measures in the Tuscany Region. Geographic Multi-Criteria Analysis - Gabbrielli, Emanuele (Italian Review of Agricultural Economics, 2016)
Agro-environmental policies are taking increasing importance in community strategies and represent the main instrument for financing Rural Development Programs (RDP). The difficulty of assessing real environmental effectiveness is one of the elements characterizing agro-environment measures. This difficulty is essentially related to the problem of identifying suitable parameters for evaluating farms according to their impact on territory. The research aimed at providing an analytical model suitable to different territorial situations. Organic and integrated farms, financed by Tuscany region with Rural Development Plans 2007-2013, were evaluated through the use of Multi-criteria Geographical Analysis. Farms were classified according to their environmental impact, through multidimensional indicators. In particular, a simulation on economic and environmental effects of EU funding budget reductions, using geo-referenced data was conducted. The implemented methodological approach was a helpful tool to assist Policy Makers in their own decisions, in ex-ante, interim, ex-post analysis, and also in the preparation of new measures on programming 2014-2020.